2011
DOI: 10.3109/00016489.2011.636378
|View full text |Cite
|
Sign up to set email alerts
|

Long-term middle ear pressure measurements in inner ear disorders

Abstract: Significant negative middle ear pressure were seen in patients with Meniere's disease compared with patients with sudden hearing loss and healthy subjects (p < 0.01). Average middle ear pressure in patients with Meniere's disease was -43 daPa, in patients with sudden hearing loss it was 2 daPa, and in healthy subjects it was 4 daPa. Patients with Meniere's disease showed a large variability of pressure values ranging from strongly pathological to normal values during long-term measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…A striking result that reinforces the muscle interpretation is the study by Park [19] of middle ear pressure in normal and in Meniere's patients. It has already been suggested that Meniere's disease is caused by excessive activity of the tensor tympani [4], so it is highly relevant that the mean middle ear pressure of 30 normals was found to be 4 daPa (±5 daPa) whereas the figure for 33 Meniere's patients was -43 daPa (±75 daPa).…”
Section: Findings From Meniere's Diseasesupporting
confidence: 61%
See 1 more Smart Citation
“…A striking result that reinforces the muscle interpretation is the study by Park [19] of middle ear pressure in normal and in Meniere's patients. It has already been suggested that Meniere's disease is caused by excessive activity of the tensor tympani [4], so it is highly relevant that the mean middle ear pressure of 30 normals was found to be 4 daPa (±5 daPa) whereas the figure for 33 Meniere's patients was -43 daPa (±75 daPa).…”
Section: Findings From Meniere's Diseasesupporting
confidence: 61%
“…Intriguingly, however, a later paper by one of the same authors [23] backs away from the association between negative middle ear pressure and Meniere's, claiming only that, based on a larger sample, the incidence of Type C (or B) tympanograms was only about the same as what Jerger found in normals. We are not told much about the change in outlook apart from enlarged numbers, but given the strong findings of the earlier work, and the equally strong findings reported later by Park (2012) [19], one might reasonably suspect that something peculiar is going on and that perhaps a key factor may have been missed. Closer investigation might provide the necessary clues, and in any such work the tensor tympani hypothesis stands as a good candidate for resolving these peculiar anomalies.…”
Section: Findings From Meniere's Diseasementioning
confidence: 83%
“…Furthermore, Morinaka and Nakamura found an increased difference of middle ear pressure between bilateral ears in MD patients 90 . Finally, patients with MD showed on average a significant negative middle ear pressure, - 43 decapascals, compared with healthy subjects and patients with sudden hearing loss 91 . Given these findings, due to the previously described importance of the cochlear aqueduct and its functional anatomic proximity to the round window, inner ear disorders such as ELH present conditions in which abnormal middle ear pressures might trigger or worsen vertigo attacks.…”
Section: Discussionmentioning
confidence: 85%
“…The abnormal middle ear pressure (type C tympanogram) is generally defined as below −100 daPa [19,20]. However, other studies have also defined abnormal middle ear pressure as below −50 daPa [9][10][11]17,21]. More recently, a prospective study by Parsel et al suggested a cut-off value for abnormal middle ear pressure to be between 25-50 daPa [22].…”
Section: Discussionmentioning
confidence: 99%
“…The oETD group consisted of 19 ears from 14 patients. Additional inclusion criteria for the oETD group were (1) presentation of typical symptoms; and (2) middle ear pressure below −50 daPa or retracted tympanic membrane [9][10][11]. The exclusion criteria were (1) perforated tympanic membrane; (2) otitis media; and (3) not having a distinctive peak in impedance audiometry (e.g., type B).…”
Section: Subject Enrollmentmentioning
confidence: 99%